Characteristics of Pain Modulation, Personality Traits and Brain Resting-State Functional Connectivity in Healthy Subjects with Low Versus High Sensitivity to Pain - Grouper, Hadas; גרופר, הדס (ProQuest Dissertations & Theses, 2021)
There is a huge variation between individuals in their sensitivity to pain. This variation consists of biological, psychological, and social components. In fact, there is no common point at which everyone will experience pain in relation to a specific noxious stimulus, and different individuals can tolerate different levels of pain to varying degrees. Over the years, studies have identified factors associated with individuals’ sensitivity to pain. These include demographic characteristics, personality traits, sensory features, and genetic components. Furthermore, neuroimaging has shown that variations in the experience of pain are represented in certain distributed brain areas. Indeed, the subjective experience of pain is dependent on the connectivity between these cerebral pain-related brain regions and expressed through different neural patterns. So far, studies that have examined the relationships between various biopsychosocial factors and experimental pain responses have shown inconsistent findings, warranting the need for continued research. Further investigation is also needed to understand the relationship between pain perception and various brain patterns of functional connectivity during the resting state (rsFC).This dissertation aimed to identify factors contributing to the variability in individuals’ sensitivity to pain. This is of great clinical importance in being able to advance the management and treatment of patients suffering from pain.The overall aim of this research was to characterize the pain modulation profile, personality traits and neural brain patterns in two extreme groups of healthy subjects ('low sensitivity to pain' [LSP] and 'high sensitivity to pain' [HSP]). Specifically, we aimed to:1) Characterize the psychophysical profiles of these two groups based on tolerance to cold pain (CPT).2) Test psychological factors and their differences in these groups.3) Explore differences in resting state functional connectivity across pain-related brain regions between these groups.For these purposes, the following tools were used:1) Quantitative sensory testing (QST), including static (pain threshold, tolerance and intensity), and dynamic tests (Conditioned Pain Modulation [CPM] and Temporal Summation [TS]).2) Self-report psychological questionnaires for evaluating different personality traits (i.e., pain catastrophizing scale [PCS] and the five factor personality traits [NEOFFI]).3) Resting state fMRI neuroimaging for testing the neural functional connectivity between pain-related brain regions and their association with cognitive-affective pain-related factors.Using these diverse tools helped to:1) Learn about the relationship between the magnitude of CPM and the sensitivity to pain.2) Examine the differences and relationships between personality traits and sensitivity to pain.3) Explore the differences between the high and low sensitivity to pain groups in their rsFC across brain regions that contribute to the experience of pain.4) Test the relationships between these rsFC brain patterns and cognitive-affective painrelated factors in the high and low sensitivity to pain groups.This dissertation is presented in the format of a collection of three articles. Each one addresses a different component that may contribute to the sensitivity to pain in healthy individuals. PAPER I was published in Neuroscience Letters (2019). PAPER II has been recently published in Journal of Pain Research. PAPER III is under second revision in the European Journal of Pain.